(untitled) (Patan Pragya, 2024)
In this work, we study the mathematical models of flows for some biofluids. In biomechanics, peristaltic flow plays an important role in which the motion generated in the fluid contained in a distensible tube when a progressive wave of area contraction and expansion travels along the wall of the tube. We consider the effect of elasticity of the tube wall in the flow through the progressive wave travelling along its length without its direct calculation. Since the no – slip condition has used on a moving undulating wall surface, it determines the sinusoidal boundary conditions on the upper and lower wall of the tube. The wide occurrence of peristaltic motion gives its result physiologically from neuro-muscular properties of any tubular smooth muscle.